2004
DOI: 10.1038/nn1279
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of immediate and future rewards differentially recruits cortico-basal ganglia loops

Abstract: Evaluation of both immediate and future outcomes of one's actions is a critical requirement for intelligent behavior. Using functional magnetic resonance imaging (fMRI), we investigated brain mechanisms for reward prediction at different time scales in a Markov decision task. When human subjects learned actions on the basis of immediate rewards, significant activity was seen in the lateral orbitofrontal cortex and the striatum. When subjects learned to act in order to obtain large future rewards while incurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
245
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 685 publications
(283 citation statements)
references
References 47 publications
29
245
3
Order By: Relevance
“…Previous work implicated anterior regions of the medial prefrontal cortex in goal representation (13)(14)(15)25), altruistic punishment (5), prediction of future rewards (14,18,26), and implicit or explicit moral appraisals (11,16,27,28). Our results indeed showed that costly decisions (choosing to costly donate or to costly oppose), which are altruistic in essence, were associated with activation of the anterior prefrontal cortex, including the frontopolar cortex and the medial frontal gyrus (BA 10͞11͞32; Fig.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Previous work implicated anterior regions of the medial prefrontal cortex in goal representation (13)(14)(15)25), altruistic punishment (5), prediction of future rewards (14,18,26), and implicit or explicit moral appraisals (11,16,27,28). Our results indeed showed that costly decisions (choosing to costly donate or to costly oppose), which are altruistic in essence, were associated with activation of the anterior prefrontal cortex, including the frontopolar cortex and the medial frontal gyrus (BA 10͞11͞32; Fig.…”
Section: Resultssupporting
confidence: 72%
“…The mesolimbic system regulates overall reward reinforcement and prediction and is activated by a host of stimuli, including food, sex, drugs, and money (11,14,18). The subgenual area, which specifically was recruited by donations, comprises a primitive paralimbic, four-layered archicortex densely interconnected with the mesolimbic dopaminergic and dorsal raphe serotonergic pathways (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a similar pattern of mesocorticalmesolimbic activation has been observed during immediate monetary and aesthetic rewards (50)(51)(52)(53), self-reported happiness (54), and the subjective funniness of cartoons (26,27). Electrical stimulation of the NAcc also results in laughter and giddiness (55).…”
Section: Figmentioning
confidence: 59%
“…This suggests that serotonin mediates decision making in healthy volunteers by modulating the processing of reward cues (Rogers et al, 2003), perhaps by facilitating the evaluation of future rewards (Schweighofer, Tanaka, & Doya, 2007), which in turn suggests that serotonin functionality corresponds to the value parameter of the subjective expected utility model. Serotonergic neurons project into the basal ganglia, controlling phasic dopamine release into the striatum, and thereby the time scale of reward prediction, modulating the adequate computation of reward prediction errors (Schweighofer et al, 2007;Tanaka et al, 2004). It therefore seems plausible that serotonin functionality corresponds not only to the value parameter but also to the probability parameter.…”
Section: Brain Areas Associated With the Value Parametermentioning
confidence: 99%